Self-control and disciplined behaviour of Buddhist students at Gangga North Lombok public junior high school 3 - Puja Yanti; Sidartha Adi Gautama; Komang Sutawan (Universitas Sebelas Maret, 2025)
Self-control, or the ability to regulate oneself, is very important to apply in today's era because by having self-control, a person can think more rationally, manage emotions, and act wisely in facing various increasingly complex challenges and temptations in the modern age. This study aims to determine the effect of self-control on the disciplined behaviour of Buddhist students at SMP Negeri 3 Gangga, North Lombok. The problems found include students who are less able to control themselves, such as being rude, often late, skipping lessons, not being responsible for assignments, and not caring about the school environment. This study is expected to improve student discipline in order to create a conducive learning atmosphere and better social ethics in the school environment. Self-control plays an important role in shaping students' disciplined behaviour. With good self-control, students can develop critical thinking skills, evaluate actions, and act more responsibly. This study employs a quantitative approach using a survey method on 99 respondents. The respondents in this study were 29 students in Year 7, 28 students in Year 8, and 42 students in Year 9. This study was conducted at SMP Negeri 3 Gangga, North Lombok, with respondents from Year 7, 8, and 9 students in the 2024/2025 academic year. The results of the regression analysis show that self-control has a positive and significant influence on students' disciplined behaviour. However, disciplined behaviour is also influenced by other factors such as family, school, and peer environments. This finding confirms that self-control is an important component in the formation of discipline, but external factors also have a major contribution in shaping students' character and self-development.